Analisis Soal HOTS pada Soal Latihan Bahasa Indonesia Kelas IX dalam Fitur Aplikasi Ruang Guru (Journal of Applied Linguistics and Literature, 2024)
This research aims to: identify the form of HOTS questions at the analyzing (C4), evaluating (C5), and creating (C6) levels of Indonesian language practice questions for class IX SMP on the Ruang Guru application. This type of research is descriptive qualitative. The research instrument used is documentation research. The research results show that: HOTS form at analyzing level (C4) with indicators of distinguishing, organizing and attributing, HOTS question form at evaluating level (C5) with indicators examining and criticizing. Finally, form HOTS questions at the creating level (C6) with implementing indicators.